Concept and Function Of Educational Management In Islamic Perspective - Ani Apiyani (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This study discusses the concept of educational management from an Islamic perspective, especially regarding how the concept and function of educational management are applied. This study is a literature study with a qualitative approach. The results of the study indicate that in the view of Islamic teachings, everything must be done neatly, correctly, orderly, and regularly. The processes must be followed properly, and something should not be done carelessly. Furthermore, the function of educational management from an Islamic perspective cannot be separated from the function of management in general, so that the function of educational management from an Islamic perspective is as follows: first, planning in educational management from an Islamic perspective must be the first step that is truly considered by managers and administrators of education; second, organizing in educational management from an Islamic perspective must be consistent with the principles that design the organization's journey, namely freedom, justice, and deliberation; third, direction in educational management from an Islamic perspective must be based on religious principles to co-workers, so that the person carries out his duties seriously and enthusiastically with deep sincerity; and fourth, supervision in educational management from an Islamic perspective must be material and spiritual, monitoring not only by managers, but also by Allah SWT, using humane methods that uphold human dignity.